(untitled) (Oshada, 2025)
The nutritional status of primary school children remains a public health concern, particularly in rural areas where socioeconomic constraints and limited access to nutritious food persist. Understanding the factors associated with children’s nutritional status is essential to support effective and context-specific interventions. This study aimed to analyze factors associated with the nutritional status of primary school children in Suco Catral Caraic, Posto Administrativu Letefoho, Municipiu Ermera, Timor-Leste. A quantitative cross-sectional study was conducted among 384 primary school children using total sampling. Data were collected through structured interviews with parents or guardians and anthropometric measurements of children. The variables analyzed included age, sex, parental education, household economic status, daily dietary intake, and children’s health history. Data analysis was performed using Chi-Square tests and multinomial logistic regression. The proportion of children with normal nutritional status was 47.7%. Bivariate analysis showed no significant association between age (p = 0.956) or sex (p = 0.936) and nutritional status. Significant associations were observed between nutritional status and maternal education (p = 0.000), paternal education (p = 0.007), household economic status (p = 0.029), daily dietary intake (p = 0.000), and health history (p = 0.000). Multinomial logistic regression indicated that the model explained 50.2% of the variance in nutritional status (Nagelkerke R² = 0.502). Maternal education emerged as the most dominant factor (χ² = 87.118; p = 0.000), followed by dietary intake and health history. Maternal education, daily dietary intake, and health history were the strongest factors associated with the nutritional status of primary school children, whereas age and sex were not significantly related. These findings highlight the importance of family-based approaches and improved dietary practices to enhance child nutritional outcomes in rural settings.